Contribution to the knowledge of the preimaginal stages of the genus Smicridea McLachlan in South America (Trichoptera: Hydropsychidae: Smicrideinae) - Sganga, Julieta Valeria; Fontanarrosa, María Soledad (Zootaxa, 2006)
Species of Smicridea occur in South and Central America, the major islands of the Antilles, and in the southwestern United States. Of the 172 known species in the genus, the preimaginal stages of only 16 have been described. In the present work, the larvae and pupae of 5 species of Smicridea are described from South America: S. (Smicridea) annulicornis (Blanchard), S. (Rhyacophylax) dithyra Flint, S. (S.) frequens (Navás), S. (R.) pampeana Flint and S. (R.) spinulosa Flint. Smicridea (R.) dithyra Flint is recorded for the first time from South America.